2023
DOI: 10.3390/jcm12144823
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Patients Living with Wilson Disease in Spain: A Cross-Sectional Observational Study

Zoe Mariño,
Marina Berenguer,
Luis Peña-Quintana
et al.

Abstract: Wilson disease (WD) is a rare copper metabolism disorder caused by mutations in the ATP7B gene. It usually affects young individuals and can produce hepatic and/or neurological involvement, potentially affecting health-related quality of life (HRQoL). We assessed HRQoL in a cohort of Spanish patients with WD and evaluated disease impact on several domains of patients’ lives, treatment adherence, drug preference and satisfaction, and healthcare resource utilisation in a cross-sectional, retrospective, multicent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In this study, the authors want to explore the mechanism of emotional expression in the study group of children and adolescents with WD and the potential impact on the level of QoL. In another study 12 on the QoL of WD patients, it was found that as many as 30% of patients reported a deterioration in their emotional state with accompanying anxiety and depression. The results of this study indicated that WD affects patients' health-related quality of life (HRQoL), particularly in the emotional aspect.…”
Section: What Is Newmentioning
confidence: 99%
“…In this study, the authors want to explore the mechanism of emotional expression in the study group of children and adolescents with WD and the potential impact on the level of QoL. In another study 12 on the QoL of WD patients, it was found that as many as 30% of patients reported a deterioration in their emotional state with accompanying anxiety and depression. The results of this study indicated that WD affects patients' health-related quality of life (HRQoL), particularly in the emotional aspect.…”
Section: What Is Newmentioning
confidence: 99%